2018
DOI: 10.1007/s00401-018-1854-7
|View full text |Cite|
|
Sign up to set email alerts
|

DNA methylation-based reclassification of olfactory neuroblastoma

Abstract: Olfactory neuroblastoma/esthesioneuroblastoma (ONB) is an uncommon neuroectodermal neoplasm thought to arise from the olfactory epithelium. Little is known about its molecular pathogenesis. For this study, a retrospective cohort of n = 66 tumor samples with the institutional diagnosis of ONB was analyzed by immunohistochemistry, genome-wide DNA methylation profiling, copy number analysis, and in a subset, next-generation panel sequencing of 560 tumor-associated genes. DNA methylation profiles were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 56 publications
4
52
2
Order By: Relevance
“…They showed that the basal‐like subgroup includes poorly differentiated tumors with a high expression of embryonic genes and a shorter survival for patients sharing some similarities with our cohort of pediatric ENBs (poor survival, dedifferentiated tumor, high Ki67). Interestingly, basal‐like ENBs harbor IDH2 mutations in one‐third of cases that might represent a therapeutic option …”
Section: Discussionmentioning
confidence: 99%
“…They showed that the basal‐like subgroup includes poorly differentiated tumors with a high expression of embryonic genes and a shorter survival for patients sharing some similarities with our cohort of pediatric ENBs (poor survival, dedifferentiated tumor, high Ki67). Interestingly, basal‐like ENBs harbor IDH2 mutations in one‐third of cases that might represent a therapeutic option …”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation was found in aggressive tumors compared with low-grade ones [18], and the tumorigenic properties of NB was inhibited by reversing epigenetic changes in CpG island with demethylating agent [19]. Capper et al reported that DNA methylation patterns might be useful for the accurate classification of olfactory NB [20]. In this study, we analyzed the methylation data of NB in TARGET database, and found that the DNA methylation in the whole-genome that was associated with MKI, an indicator of NB histological classification [7], was significantly related to prognosis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…As such, despite morphological and immunophenotypical consistency, improved diagnostic methods are much needed. A recent study conducted by Capper et al (2018) showcased the reliability of methylation-based tumour profiling for more accurate diagnosis using a classifier system developed for brain tumours [ 10 ••, 11 ]. Furthermore, their study highlighted the likely prevalence of misdiagnosis in this malignancy and suggested that histology alone may frequently misdiagnose cases.…”
Section: Novel Biomarkers In Olfactory Neuroblastomamentioning
confidence: 99%